(untitled) (Bulletin of criminological association of Ukraine, 2023)
The article is devoted to the topical issues of implementing international standards for ensuring the right to privacy in the private life of a person in criminal proceedings. The author identifies the historical background for the formation of the right to privacy, its essence and significance are determined. It is established that the heyday of the introduction of international standards of the right to privacy life of a person occurred in the period after the Second World War in 1945, when there was an urgent need for effective protection of human rights arose. The article analyzes international legal documents that first enshrined international standards for ensuring human rights in general and the right to privacy in particular, in particular. The author outlines national legal acts that define the principles of non-interference in a person’s private life. It is determined that the basis of national legislation in the field of human rights protection is based on international legal standards for the promotion and protection of human rights, in particular, those set out in the European Convention. The author emphasizes the importance of the principle of non-interference with the private life of a person during criminal proceedings is emphasized. The essence of the of the legal regulation of international standards of non-interference with theprivate life of a person is determined. It is concluded that the study of international standards of human rights are the key to a clear implementation of the latter in national legislation and practice of its application.